2016
DOI: 10.1002/jip.1461
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of registered sexual offenders in an Australian jurisdiction

Abstract: Current policies to manage convicted sexual offenders living in the community do not differentiate between those at different levels of risk. This is important if risk management strategies are to be better targeted. However, current methods of categorizing risk bands rely on the application of data from other populations, and thus may lack validity when used in jurisdictions other than those in which the validation data were collected. This study provides a descriptive analysis of cases managed by police in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…Data from six international studies demonstrated the RM2000 had better predictive ability than comparable measures (Hanson and Morton-Bourgon, 2009). Day et al (2016) found very few ‘low’ risk offenders assessed using the RM2000 had reoffended (2%) compared with those assessed as medium, high or very high (recidivism range: 53 to 58%), highlighting its predictive ability. However, in one Australian study that attained perceptions of police who operate the sex offender registry, the police described the RM2000 as crude because it did not take dynamic factors into account such as living conditions, social support and case management, and circumstances particular to the offence (Powell et al, 2014).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Data from six international studies demonstrated the RM2000 had better predictive ability than comparable measures (Hanson and Morton-Bourgon, 2009). Day et al (2016) found very few ‘low’ risk offenders assessed using the RM2000 had reoffended (2%) compared with those assessed as medium, high or very high (recidivism range: 53 to 58%), highlighting its predictive ability. However, in one Australian study that attained perceptions of police who operate the sex offender registry, the police described the RM2000 as crude because it did not take dynamic factors into account such as living conditions, social support and case management, and circumstances particular to the offence (Powell et al, 2014).…”
Section: Resultsmentioning
confidence: 97%
“…The Risk Matrix 2000 (RM2000) is a statistically derived risk assessment tool that helps classify potential recidivism of registered sex offender groups and is widely used (Day et al, 2016; Kewley and Blandford, 2017; Powell et al, 2014; Whitting et al, 2017). In fact, the RM2000 is the industry standard throughout the criminal justice system in the UK and, in particular, provides the police with direction on coordinating resources (Kewley and Blandford, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations